Semen Quality and Sperm DNA Integrity in Patients With Severe Active Inflammatory Bowel Disease and Effects of Tumour Necrosis Factor-alpha Inhibitors. (30th November 2018) - Grosen, Anne; Bungum, Mona; Christensen, Lisbet Ambrosius; Cordelli, Eugenia; Larsen, Ole Halfdan; Leter, Giorgio; Julsgaard, Mette; Vestergaard, Thea; Villani, Paola; Hvas, Christian Lodberg; Kelsen, Jens
Abstract: Background and Aims: The impact of severe inflammation on semen quality, including sperm DNA integrity, in men with inflammatory bowel disease [IBD] is unknown, as are the potential effects of anti-tumour necrosis factor-alpha [TNF-alpha] therapy. We investigated the influence of severe active IBD and anti-TNF-alpha treatment on semen quality. Methods: We prospectively included 20 patients admitted with severe active IBD. Further, 19 patients who initiated and 17 who stopped anti-TNF-alpha therapy were included. Semen samples were obtained during active disease, and on/off treatment. For paired comparisons, samples were collected not less than 3 months after achieving remission, after treatment initiation, or after treatment cessation. Sperm DNA Fragmentation Index [DFI], concentration, morphology, and motility were evaluated. Sex hormones and seminal plasma anti-TNF-alpha drug levels were measured. Results: In patients with severe disease, progressive sperm motility was impaired and increased significantly [from 28.4% to 37.4%, p = 0.045] during remission. There was no difference in DFI [12.5% versus 12.0%, p = 0.55], concentration [55.0 mill/ml versus 70.0 mill/ml, p = 0.39], or normal morphology [4.7% versus 5.1%, p = 0.51] in these patients. During active disease, testosterone was decreased, and normalised after obtaining remission. Patients who started anti-TNF-alpha therapy had a statistically significant, but clinically irrelevant, reduction in DFI after treatment initiation [12.8% versus 10.0%, p = 0.02]. All other semen parameters were unaffected by therapy. Anti-TNF-alpha drugs were excreted in negligible amounts in semen. Conclusions: Severe active IBD reduces progressive sperm motility and testosterone levels, but sperm DNA integrity is unaffected by active disease. Anti-TNF-alpha therapy does not impair sperm quality.